Physico-chemical Characterization and In Vitro Evaluation of Biopharmaceutics Classification System Class II Drug Febuxostat - Sundari, P. Tripura (Asian Journal of Pharmaceutics (AJP), 2016)
Aim: Febuxostat (FBX) is a non-purine selective inhibitor of xanthine oxidase/xanthine reductase. It belongs to Biopharmaceutics Classification System Class II with low solubility and high permeability. Because of low solubility, the bioavailability of the drug is hampered, food also interferes with the absorption of the drug and decreases the Cmax by 38-49%. The bioavailability of a drug is a function of dissolution rate of the drug which is controlled by the surface area of the drug. In the category of poorly soluble drugs, the change in surface area of the drug will show considerable changes in the solubility and dissolution of the drug. Materials and Methods: In the present study, the attempts were made to improve the bioavailability of FBX by solid dispersions technique by employing poly vinyl pyrrolidone K30 (PVP K30) and hydroxy propyl methyl cellulose E15 (HPMC E15) as carrier molecules. Different ratios on weight basis were prepared, viz., 1:1,1:2,1:3,2:1 with PVP and 1:1, 1:2, 1:3,1:4 with HPMC were prepared. Results and Discussion: These preparations were characterized in liquid state by phase solubility studies and in solid state by differential scanning calorimetry, Fourier transform infrared spectroscopy, Powdered X-ray diffraction studies, and scanning electron microscopy. The aqueous solubility of FBX is favored by the presence of both the carriers. Solid state characterization indicated that FBX was present as fine amorphous form in the carrier polymeric molecules. Conclusion: In contrast to the solution rate of pure FBX, the dissolution of drug in carriers considerably improved the dissolution rate, this can be attributed to the increased wettability and dispersibility as well as decreased crystallinity and increased amorphous fraction of the drug